3D‐Printed Flexible Piezoresistive Sensors for Stretching and Out‐of‐Plane Forces. Issue 11 (18th August 2021) - Xiang, Dong; Zhang, Zixi; Wu, Yuanpeng; Shen, Jiabin; Harkin‐Jones, Eileen; Li, Zhenyu; Wang, Ping; Zhao, Chunxia; Li, Hui; Li, Yuntao
Abstract: Conductive polymer composites (CPCs) of carbon nanotubes (CNTs) and graphite nanosheet (GNP)‐filled thermoplastic polyurethane (TPU) are 3D‐printed into flexible piezoresistive sensors via fused filament fabrication. The sensor, with a customized lever‐cross structure, allows detection of stretching and out‐of‐plane forces of different magnitudes and frequencies. The out‐of‐plane force direction is obtained by combing the relative electrical resistance change in the cross section of the sensor with a force analysis. The 75‐CNT/25‐GNP sensor (CNT‐to‐GNP mass ratio of 75%‐to‐25%) demonstrates excellent sensing performance at a total nanoparticle loading of 3 wt%. The linearity of the 75‐CNT/25‐GNP sensor is 0.98, while those of the 100‐CNT and 50‐CNT/50‐GNP sensors are 0.93 and 0.86, respectively. The gauge factor of the 75‐CNT/25‐GNP sensor is 52% higher than that of the 100‐CNT sensor, and its sensing strain range is 79% above that of the 50‐CNT/50‐GNP sensor. Excellent sensing stability is demonstrated for the 75‐CNT/25‐GNP sensor after 1500 stretching (out‐of‐plane force) cycles. The synergistic effect of CNTs and GNPs on sensing performance of piezoresistive sensors is clearly shown in this study. Abstract : Conductive polymer composites (CPCs) of carbon nanotubes (CNTs) and graphite nanosheet (GNP)‐filled thermoplastic polyurethane (TPU) are 3D‐printed into flexible piezoresistive sensors via fused filament fabrication. The sensor, with a customized lever‐cross structure, allows detection of stretching and out‐of‐plane forces of different magnitudes and frequencies. This work provides valuable information for the design and fabrication of multifunctional piezoresistive sensors.